Some azine and azole derivatives as antioxidant additives for lithium lubricating grease - Reda M. Fikry; Refaat A. El-Adly; Nabila A. Ismail; A.S. El-Tabei; Hend Al-Aidy (Egyptian Journal of Petroleum)
Lubricating greases undergo extensive deterioration under the operation conditions and storage. Hydrocarbon chain is one of the major factors resulting in loss of the base fluid quality by formation of products having negative effects on the physicochemical properties in particular the total acid number and dynamic viscosity. Antioxidants are major ingredients that protect the quality of lubricating grease by retarding oxidation reactions. Accordingly, the aim of this paper is a study on the preparation and evaluation of some compounds which act as antioxidants for prepared lithium lubricating grease. These additives are α-(2-amino-3-cyano-6-pyridyl)o-hydroxyl cinnamic hydrazide (compound I), ethoxymethyl enamino derivative (compound II) and 3-amino-5-hydroxyl-4 phenylazo-1H-pyrazole (compound III). The structure of these compounds has been confirmed using elemental analysis, nuclear magnetic resonance and infrared spectroscopy. On the other hand, lithium lubricating grease was prepared and evaluated according to the National Lubricating Grease Institute (NLGI) and Egyptian Standard (ES). The antioxidant compounds were tested for the prepared grease with concentration 0.1 wt.%. The efficiency of these compounds has been determined using total acid number. It was found that the prepared lithium grease resists oxidation reaction in the presence of these compounds. A correlation between the chemical structure of these compounds and their efficiency as antioxidants additives was discussed. Data showed that the efficiency of these compounds as antioxidants decreases in the order: compound I > compound II > compound III.